Short Attention Spans in EFL Learning: A Descriptive Qualitative Study of Cognitive Characteristics, Skill-Specific Impacts, and Instructional Strategies - Uas Gna; Washlurachim Safitri; Epi Wadison; Solehan (Teaching English and Language Learning English Journal, 2026)
The increasing prevalence of short attention spans in digitally mediated learning environments presents significant challenges for English as a Foreign Language (EFL) instruction. This descriptive qualitative study investigates (1) the behavioral and cognitive characteristics of short attention spans among EFL learners, (2) their effects on vocabulary development, reading fluency, and listening comprehension, and (3) instructional strategies that may mitigate their negative impact. Conducted in a natural classroom setting at the university level, the study employed purposive sampling and collected data through in-depth interviews, structured observations, and document analysis. Data were analyzed inductively through data reduction, data display, and conclusion drawing, with triangulation ensuring credibility. The findings indicate that short attention spans are reflected in task-switching behavior, digital distraction, and mind-wandering, which disrupt sustained cognitive engagement. Listening comprehension was found to be the most vulnerable skill due to the transient nature of auditory input, while reading fluency and vocabulary retention were also adversely affected by attentional fragmentation. However, pedagogical strategies such as task chunking, interactive learning, multimodal instruction, and structured breaks were identified as effective in enhancing attentional stability. The study underscores the importance of integrating attention management into EFL instructional design to improve learner engagement and learning outcomes.